The effect of tourniquet reperfusion interval on malondialdehyde (MDA) level and skeletal muscle damage in the treatment of long bone fractures - Adhi Satriyo Utomo; Thomas Erwin Christian Junus Huwae (Medicinski glasnik, 2026)
Aim: Tourniquets are commonly used during surgery to control bleeding; however, their application can lead to complications, including ischemic reperfusion injury. Post-tourniquet syndromes such as pain, swelling, and muscle weakness may persist for up to six weeks. Aim: of this study was to investigate the reperfusion interval duration to prevent muscle tissue damage. Methods: This experimental study involved 48 male white rats (Rattus norvegicus) with induced tibial fracture. The rats were divided into two groups, A and B, with each group receiving four different treatments, resulting in a total of eight groups. The control groups (A1 and B1) had the tourniquet applied for 3 hours, while other groups had it used for 2 hours, followed by 5, 10, and 15-minute reperfusion intervals. Group A was sacrificed one hour post-deflation, and Group B was sacrificed on day 14. Malondialdehyde (MDA) level and muscle histology were analysed using one-way ANOVA. Results: In group A, significant difference was found between the 10 and 15-minute reperfusion intervals. In group B, the 10-minute reperfusion interval showed the most favourable outcome, with a 42.63% reduction in injury for group A and a 32.27% reduction for group B. Significant differences in MDA level was found between the control and reperfusion groups in both groups A and B. Conclusion: The 10-minute reperfusion interval effectively reduces ischemic reperfusion injury in muscle tissue, as indicated by lower MDA level and less muscle damage. This interval optimally restores aerobic metabolism and prevents excessive reactive oxygen species (ROS) production.
Keywords: malondialdehyde; reperfusion injury; tourniquet